Which self-management strategies do health care professionals recommend to their cancer patients?: An experimental investigation of patient age and treatment phase - Ungar, Nadine; Schmidt, Laura; Gabrian, Martina; Haussmann, Alexander; Tsiouris, Angeliki; Sieverding, Monika; Steindorf, Karen; Wiskemann, Joachim (Journal of behavioral medicine, 2019)
This vignette based study aimed to examine recommendations of health care professionals (HCPs) in promoting self-management strategies to cancer patients. Nine-hundred-forty-two physicians and nurses were asked to (1) indicate if they would recommend self-management strategies to a vignette cancer patient, and (2) to specify those in an open format. Vignettes included a manipulation of patient age (60 vs. 75 years) and treatment phase (currently treated versus treatment completed). Six categories emerged through coding a total of 2303 recommendations: physical activity (71.8%), nutrition (64.3%), psychological support (36.7%), medical support (29.2%), conscious living (17.2%) and naturopathy (12.3%). While psychological support was particularly recommended during treatment, physical activity was more frequently recommended after completion of treatment. Results suggest that HCPs recommend a variety of self-management strategies besides standard medical treatment. Patient's treatment phase and age seem to partly influence recommendation behavior, potentially indicating insecurities regarding acute treatment situations and age-related stereotypes.
First Online: 23 October 2018
Gesehen am 12.06.2019